Exotic Textiles from Medieval Christian Church Treasuries: Circulation, Utilization, and Integration - Yu, Ruibo (Actual Problems of Theory and History of Art, 2023)
This essay focuses on a group of medieval textiles produced during the 11th–12th century in the workshops of Islamic Spain. Nevertheless, they were transported into the Occident and were conserved in church treasuries. These textiles are characterized by the decoration motifs of oriental style, such as the adaptation of the grand medallions, the images of mythical animals, and the iconography of sovereigns. The luxurious Islamic textiles were utilized, in the liturgical contexts, as chasubles or shrouds; nevertheless, it is highly probable that these textiles were originally used in architectural contexts in the Islamic world. It is supposed that the function of these reconstructed textiles relates to their original use. The conception of soft architecture in the new sphere intersected with the original function of textiles.
Keywords: Islamic textiles; Al-Andalus; Christian treasuries; soft architecture